Applying an ecosystem approach to brucellosis control: can an old conflict between wildlife and agriculture be successfully managed?. Issue 6 (1st August 2006) - Bienen, Leslie; Tabor, Gary
Abstract : Brucellosis is a hotly debated topic in the western United States. For decades, this disease has pitted conservationists against ranchers, as well as against federal and state government agencies, particularly in Montana and Wyoming. Bison and elk are the primary wildlife disease reservoirs, and cattle the primary species of agricultural concern. Here, we briefly summarize the disease's etiology and ecology in wildlife and discuss recent developments in the sociopolitical landscape and in scientific research that could result in improved management. Applying some key principles of ecosystem management is crucial to improving brucellosis control in wildlife.